Self-Disclosure dalam Meningkatkan Keterbukaan Siswa Menghadapi Masalah Pribadi dalam Bimbingan dan Konseling - Rina Marlina; Yusi Riska Yustiana; Uman Suherman; Ahman Ahman (Educational Guidance and Counseling Development Journal, 2026)
Abstract Self-disclosure is the process of revealing personal information to others and plays a vital role in identity development, emotional regulation, and the formation of healthy interpersonal relationships, especially among adolescents. However, within the Indonesian educational context, students' openness remains hindered by factors such as shame, fear of stigma, and a lack of supportive environments. This study highlights findings from the 2023 Counseling Corner program in Karawang Regency, which revealed a high level of student resistance to disclosing personal issues, even through anonymous mechanisms. It is necessary to implement guidance and counseling approaches based on safe spaces, trust-building, and the use of expressive methods such as art therapy and narrative techniques to promote self-disclosure. This approach not only supports students' emotional well-being but also serves as a preventive strategy in creating an inclusive and psychologically healthy school environment.Keywords: self-disclosure, guidance and counseling, students, psychological well-being, safe space.